2020
DOI: 10.1038/s41598-020-58362-3
|View full text |Cite|
|
Sign up to set email alerts
|

Amine oxidase 3 is a novel pro-inflammatory marker of oxidative stress in peritoneal endometriosis lesions

Abstract: Endometriosis is a common gynaecological disease of women in reproductive age, and is thought to arise from retrograde menstruation and implantation of endometrial tissue, mostly into the peritoneal cavity. The condition is characterized by a chronic, unresolved inflammatory process thereby contributing to pain as cardinal symptom in endometriosis. Elevated reactive oxygen species (ROS) and oxidative stress have been postulated as factors in endometriosis pathogenesis. We here set out for a systematic study to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 46 publications
(48 reference statements)
1
17
0
Order By: Relevance
“…Interestingly, there are several evidences that IL-8 cytokine facilitates the migration of fibroblasts and endothelial cells [ 57 ]. In endometriosis, the IL-8 levels are increased under the synthesis of the oxidative stress products (e.g., 4-hydroxy-2-nonenal) [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, there are several evidences that IL-8 cytokine facilitates the migration of fibroblasts and endothelial cells [ 57 ]. In endometriosis, the IL-8 levels are increased under the synthesis of the oxidative stress products (e.g., 4-hydroxy-2-nonenal) [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, it was shown that several inflammation-related molecules are also regulated dependently or independently of ROS production and accumulation. Thézénas et al [29] identified amine oxidase 3 and vascular adhesion protein 1 (AOC3/VAP1), in particular alkenal reductase PTGR1 and methionine sulfoxide reductase, as candidates for altered ROS landscape in EMS and possibly influencing the systemic and/or local inflammatory response. Furthermore, they observed important molecular changes in the ectopic lesion (such as iron overload, increased ROS production, and lipid peroxidation) and noted that ROS-derived 4-hydroxy-2-nonenal (4-HNE) over-production led to monocytic interleukin IL-8 release.…”
Section: Oxidative Stress and Ems Oxidative Stress And Emsmentioning
confidence: 99%
“…Due to the multitude of factors regulating the level of oxidative stress, authors highlight that there is need of further studies to conclude if there is possible use of oxidative stress markers as diagnostic tests for endometriosis [9,44].…”
Section: Oxidative Stressmentioning
confidence: 99%